Implementasi Aplikasi Sistem Informasi Akuntansi Penjualan dan Kasir Digital Berbasis Android "Loyverse Pos" dalam Penyusunan Laporan Penjualan - Fathur Rasyid Ridha; Iyeh Supriatna (Indonesian Accounting Literacy Journal, 2023)
The development of the times has made the era of business competition begin to change towards sales made online. Toko Kramat Jaya is a retail store that sells various daily needs that use a conventional cash register for a sales accounting information system that is being implemented so that it has limitations in generating information about sales. In this regard, this study aims to help Toko Kramat Jaya Cimahi to solve problems encountered regarding sales by building an application setup and then implementing the Loyverse POS digital cashier application. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques used are interviews, observation, and documentation. The results of this study are in the form of guidelines in building the application and how the impact of implementing Loyverse POS is in improving the quality of the sales accounting information system that is being implemented.